European milestones in the protection of workers’ claims in the case of insolvency - Karaleu, Yury Y. (Europejskie kamienie milowe w ochronie roszczeń pracowników w przypadku niewypłacalności, 2021)
The employer’s insolvency entails, in addition to the potentially devastating economic consequences of output reduction and the disruption of economic relations, adverse social costs for employees – the loss of jobs and earnings. It is not only the employee and his or her family who suffer a great loss, but the whole community. Thus, society faces the serious question of how to ensure the payment of wages to employees in the case of insolvency and provide a solid framework with which countries can find durable solutions, effectively organise and manage the protection of workers’ claims. This paper analyses the achievement in developing European and national systems of protection of workers’ claims in cases of insolvency, and shows the progress made by EU countries in arriving at a balance of interests between employers, employees and society in the protection of outstanding claims of employees in the event of their employer’s insolvency
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 1, s. 22-36
Keywords: insolvency; employees' claims; EU directives; niewypłacalność; roszczenia pracowników; dyrektywy Unii Europejskiej